Additive Engineering to Grow Micron‐Sized Grains for Stable High Efficiency Perovskite Solar Cells. Issue 18 (26th July 2019) - Li, Hua; Wu, Guohua; Li, Wanyi; Zhang, Yaohong; Liu, Zhike; Wang, Dapeng; Liu, Shengzhong (Frank)
Abstract: A high‐quality perovskite photoactive layer plays a crucial role in determining the device performance. An additive engineering strategy is introduced by utilizing different concentrations of N, 1‐diiodoformamidine (DIFA) in the perovskite precursor solution to essentially achieve high‐quality monolayer‐like perovskite films with enhanced crystallinity, hydrophobic property, smooth surface, and grain size up to nearly 3 µm, leading to significantly reduced grain boundaries, trap densities, and thus diminished hysteresis in the resultant perovskite solar cells (PSCs). The optimized devices with 2% DIFA additive show the best device performance with a significantly enhanced power conversion efficiency (PCE) of 21.22%, as compared to the control devices with the highest PCE of 19.07%. 2% DIFA modified devices show better stability than the control ones. Overall, the introduction of DIFA additive is demonstrated to be a facile approach to obtain high‐efficiency, hysteresis‐less, and simultaneously stable PSCs. Abstract : A N, 1‐diiodoformamidine (DIFA) additive is introduced in the perovskite precursor to attain high efficiency and stable perovskite solar cells (PSCs). Upon the addition of 2% DIFA, the compact, smooth, relatively hydrophobic, and large grained perovskite films are achieved with highly efficient defect passivation, which substantially increases the power conversion efficiency from 19.07% for the control device to 21.22%.